Sosialisasi Penggunaan Perangkat Teknologi Dalam Membantu Kinerja Pemerintah Di Kampung Matara - Umiyati Haris; Fransin Kontu (Kreativasi : Journal of Community Empowerment, 2024)
This community service aims to improve the performance capabilities of the village government through the socialisation of the use of technology in Matara Village, Semangga District, Merauke Regency. The socialisation of the use of technological devices not only improves the performance of the village government but also empowers the community to be more active and effective in participating in village development, which is very important because it is related to efficient and quality public services to the local community. The approach in this community service involves collaboration between the service team and the village apparatus. In this activity, the socialisation of training in the use of Microsoft Office using a laptop was carried out. In the process, the author used a participatory method that actively involved the village community in planning and implementing the programme. The results of this community service showed positive changes in improving the ability of the community and village officials to use applications to create letters. There was a significant increase in their understanding of the functions of Word and Excel features. Socialisation of the use of technological tools has an important role in improving government performance in Matara Village. Through this service activity, it is hoped that there will be an increase in awareness and understanding of the importance of technology in supporting various government and development activities in Matara Village.